Способ конверсии углеводородсодержащих газов - Гончаров И. В. Иван Васильевич; Коробочкин В. В. Валерий Васильевич; Терещенко В. А. Василий Анатольевич; Яворовский Н. А. Николай Александрович
опубл. 10.04.05